Short-term cryopreservation and thawing have minimal effects on Plasmodium falciparum ex vivo invasion profile - Thiam, Laty G.; Ansah, Felix; Niang, Makhtar; Awandare, Gordon A.; Aniweh, Yaw (Frontiers in Cellular and Infection Microbiology, 2022)
Ex vivo phenotyping of P. falciparum erythrocyte invasion diversity is important in the identification and down selection of potential malaria vaccine targets. However, due to the lack of appropriate laboratory facilities in remote areas of endemic countries, direct processing of P. falciparum clinical isolates is usually not feasible. Here, we investigated the combined effect of short-term cryopreservation and thawing processes on the ex vivo invasion phenotypes of P. falciparum isolates. Ex-vivo or in vitro invasion phenotyping assays were performed with P. falciparum clinical isolates prior to or following culture adaptation, respectively. All isolates were genotyped at Day 0 for parasite clonality. Subsequently, isolates that were successfully culture-adapted were genotyped again on Days 7, 15, 21, and 28-post adaptation. Invasion phenotyping assays were performed in isogenic isolates revived at different time points (3, 6, and 12 months) post-cryopreservation and the resulting data were compared to that from ex-vivo invasion data of matched isogenic parental isolates. Our findings indicate that natural P. falciparum infections mostly occur as polyclonal infections. We also show that short-term culture adaptation selects for parasite clonality and could be a driving force for variation in invasion phenotypes as compared to ex vivo data where almost all parasite clones of a given isolate are present. Interestingly, our data show little variation in the parasites’ invasion phenotype following short-term cryopreservation. Altogether, our data suggest that short-term cryopreservation of uncultured P. falciparum clinical isolates is a reliable mechanism for storing parasites for future use.